The Effect of Tilapia Meat Flour Addition on the Preference level of Dried Sus - Meida Maulida; Rusky Intan Pratama; Asep Agus Handaka Suryana; Iis Rostini (Grouper, 2024)
Tilapia as a food ingredient has a high nutritional content, one of which is protein content. Tilapia meat can be processed into flour, which can then be used as an ingredient to increase the nutritional content of dried sus. This study aims to determine the amount of tilapia meat flour added to produce dried sus that is most favored by panelists. The method used was an experimental method with 0%, 10%, 15%, and 20% tilapia meat meal addition. The parameters observed were the hedonic test and the proximate test. The results showed that the addition of tilapia meat flour to the most preferred dry sus was the 15% treatment with an average value of appearance of 8.0; aroma of 7.7; texture of 8.4; taste of 7.9; criterion weight of 0.57 and alternative value of 8.8. The resulting proximate test is water content of 4.86; ash content of 2.91%; protein content of 12.35%; fat content of 31.95%; and carbohydrate content of 45.52%.